Ferritic stainless steel bar and its manufacturing method
Patent Information
- Application Number
- JP2021055481
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-29
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2041-03-29
AI Technical Summary
【0015】 本発明によれば、溶接の熱影響部においても優れた耐粒界腐食性を有し、かつ鋼材中心部の靭性に優れる、フェライト系ステンレス棒状鋼材を得ることができる。靱性に優れるため、優れた鍛造性、鍛造成形性を実現することができる。
Smart Images

Figure 0007643907000001 
Figure 0007643907000002 
Figure 0007643907000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a ferritic stainless steel bar having excellent toughness and intergranular corrosion resistance, and a method for producing the same. [Background technology]
[0002] In recent years, the need for stronger environmental regulations and improved fuel efficiency has increased, and automobile exhaust system components require materials with better heat and corrosion resistance. For this reason, ferritic stainless steels are being used instead of cast iron.
[0003] Automobile exhaust systems are composed of components such as DPFs and catalytic converters that purify exhaust gas, and flanges are used to connect and secure each component. Instead of the conventional casting method, flanges manufactured by a combination of forging and cutting are increasingly being used, and there is a tendency to avoid the risk of embrittlement cracking during casting and welding. Ferritic stainless steels have excellent heat resistance and corrosion resistance, but in the heat-affected zone (HAZ) of welding, Cr deficiency near the grain boundaries reduces intergranular corrosion resistance, i.e., sensitization is likely to occur. For this reason, the C and N content is reduced and micro-alloying elements such as Nb and Ti are added, but during casting, coarse carbonitrides are more likely to precipitate in the center than on the surface side, deteriorating the toughness of the center of the steel. In particular, in thick materials with a low reduction in area or large diameter materials, it is difficult to break up the coarse carbonitrides during hot rolling, making it difficult to improve toughness, and if the center of the steel is exposed to the surface during product processing, the toughness of the product will deteriorate significantly. In addition, if hot working is not performed within the appropriate temperature range and time, the Laves phase (Fe2Nb) that causes embrittlement may precipitate, further reducing toughness.
[0004] For example, Patent Document 1 discloses a ferritic stainless steel wire having improved cold forgeability, machinability, and corrosion resistance by reducing the C and N contents and adding Nb and / or Ti. Patent Document 2 discloses a high-purity ferritic steel plate having improved formability. However, there is insufficient research into toughness and forgeability in the case of a large diameter of more than 16 mm, which is necessary for flange application.
[0005] Patent Documents 3 and 4 disclose ferritic stainless steel wire rods with excellent cold forgeability by reducing the C and N contents and adding Nb and / or Ti. On the other hand, technical studies on the intergranular corrosion resistance of the weld heat affected zone are insufficient.
[0006] Patent Document 5 discloses a high-purity ferritic steel in which the toughness of a large-diameter steel bar is improved by controlling the orientation. However, the toughness of the center of the steel is not sufficiently examined. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2014 / 157231 [Patent Document 2] JP 2020-143309 A [Patent Document 3] JP 2013-147705 A [Patent Document 4] Japanese Patent Application Publication No. 3-126843 [Patent Document 5] International Publication No. 2020 / 196595 Summary of the Invention [Problem to be solved by the invention]
[0008] An object of the present invention is to provide a ferritic stainless steel bar having good intergranular corrosion resistance even in weld heat affected zones and excellent toughness in the center of the steel, and a method for producing the same. [Means for solving the problem]
[0009] As a result of various investigations to solve the above problems, the present inventors have discovered that in a high-purity ferritic stainless steel bar having adjusted composition, hot working after casting in a temperature range higher than the Laves phase precipitation range and in the M6C precipitation range, controlling the size of the carbides to an appropriate size as M6C type, and quickly cooling the Laves phase precipitation region can improve the toughness of the steel while maintaining good intergranular corrosion resistance. In addition, they have discovered that controlling the heating temperature and time of the slab heating can control the size and distribution of coarse Nb carbonitrides in the center, thereby further improving the toughness of the steel.
[0010] The present invention has been made to solve the above-mentioned problems, and the gist of the present invention is the following ferritic stainless steel bar material and its manufacturing method. (1) Chemical composition, in mass%, C:0.001~0.03%, Si:0.01~1.0%, Mn:0.010~1.0%, Ni:0.05~3.0%, Cr:10.5~25.0%, Cu:0.02~1.0%, N:0.001~0.03%, Nb:0.10~1.0%, Mo:0~3.0%, Ti:0~0.5%, V:0~1.0%, W:0~0.50%, Zr:0~0.50%, B:0~0.010%, Al:0~0.50%, Ca:0~0.0 5%, Mg: 0~0.05%, Co: 0~0.50%, Ga: 0~0.05%, Sn: 0~0.50%, Sb: 0~0.50%, Ta: 0~0.50%, REM: 0~0.10%, The balance is Fe and impurities. The following formulas (i) to (ii) are satisfied: A ferritic stainless steel bar in which the extraction residue recovered from the bar by electrolytic extraction using a 0.2 μm mesh filter contains precipitates of Nb carbonitride and / or M6C, and the X-ray diffraction intensity of the 112 plane of the Laves phase is less than 20% of that of the 111 plane of the Nb carbonitride. 10.0≦(Nb+Ti) / (C+N) (i) 12.0≦Cr+3(Mo+Ni)+(Nb+Ti)-10(C+N)≦30.0 (ii) In the above formula, each element symbol represents the content (mass%) of each element contained in the steel, and when no element is contained, the symbol is set to zero.
[0011] (2) Chemical composition, in mass percent, 2. The ferritic stainless steel bar according to claim 1, comprising one or more selected from the group consisting of Mo: 0.01-3.0%, Ti: 0.05-0.5%, V: 0.01-1.0%, W: 0.05-0.50%, Zr: 0.010-0.50%, B: 0.0003-0.010%, Al: 0.001-0.50%, Ca: 0.0005-0.05%, Mg: 0.0005-0.05%, Co: 0.01-0.50%, Ga: 0.001-0.05%, Sn: 0.010-0.50%, Sb: 0.010-0.50%, Ta: 0.01-0.50%, and REM: 0.001-0.10%.
[0012] (3) In a cross section including the center of a bar-shaped steel material and parallel to the longitudinal and radial directions, the number density of precipitates with a maximum diameter of 5 μm or more distributed within a range of 1 / 4 of the diameter from the center of the bar-shaped steel material on both sides in the radial direction and 5 mm in the longitudinal direction is 1,000 precipitates / mm 2 The ferritic stainless steel bar according to the above (1) or (2),
[0013] (4) A ferritic stainless steel bar according to any one of (1) to (3) above, in which the transition temperature at the center of the steel is 150° C. or lower in a Charpy test.
[0014] (5) A method for producing a steel material having a chemical composition according to any one of the above (1) to (4), characterized in that the holding temperature of the slab soaking is 800 to 1250°C and the holding time is 60 to 600 minutes. (6) A method for producing a ferritic stainless steel bar according to (5) above, wherein the residence time at 1100°C or higher during hot rolling is 10 minutes or less, the total residence time at 800 to 1100°C is 30 to 300 minutes, the finishing temperature is 780 to 1100°C, the average cooling rate to 750°C is 5 to 200°C / min, and the average cooling rate from 750°C to 550°C is 50 to 500°C / min. Effect of the Invention
[0015] According to the present invention, it is possible to obtain a ferritic stainless steel bar having excellent intergranular corrosion resistance even in the heat-affected zone of welding and excellent toughness in the center of the steel. Because of the excellent toughness, excellent forgeability and forge formability can be realized. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The present invention relates to a ferritic stainless steel bar and a manufacturing method thereof. Here, the term "bar" refers to a wire rod, wire rod, or steel wire that has a uniform surface perpendicular to the longitudinal direction. The cross-sectional shape is not limited to a typical circular shape, but includes flat steel, square steel, and deformed steel that have a rectangular cross section.
[0017] The present inventors have conducted various investigations in order to obtain a ferritic stainless steel bar having excellent intergranular corrosion resistance even in the heat-affected zone of welding and good toughness in the center of the steel part. As a result, the following findings were obtained.
[0018] For example, in ferritic stainless steel rods with reduced C and N content and added Nb, the Laves phase (Fe2Nb) precipitates in needle-like shapes, which reduces toughness and tends to reduce forgeability. Dispersing in a form with an aspect ratio close to 1.0 and at a size that does not cause precipitation hardening is effective in terms of toughness. In other words, dispersing M6C (where M is an atomic ratio of (Fe+Cr) / Nb of about 1.0) in an appropriate size to soften the ferritic phase while suppressing the Laves phase is effective in improving toughness. In addition, controlling the form and distribution of carbonitrides in the center is effective in improving the toughness of the center of the steel.
[0019] The present invention has been made based on the above findings. In addition, preferred embodiments of the present invention will be described in detail. In the following description, the preferred embodiments of the present invention will be described as the present invention. Each of the requirements of the present invention will be described in detail below.
[0020] 1.Chemical composition The reasons for limiting the content of each element are as follows. In the following description, "%" for the content means "mass %."
[0021] C: 0.001 to 0.03% C has the effect of improving the strength of steel, but it is an unavoidable impurity that may reduce mechanical properties. In particular, since the precipitation of chromium carbides in the heat-affected zone of welding reduces intergranular corrosion resistance, it is desirable to reduce the C content as much as possible. In this case, if the C content exceeds 0.03%, the Nb or Ti content required for suppressing sensitization increases, and the manufacturing cost increases. Furthermore, the forgeability decreases due to the formation of Nb carbonitrides or Ti carbonitrides. For this reason, the C content is set to 0.03% or less. On the other hand, if it is attempted to reduce the C content to less than 0.001%, the manufacturing cost increases, so the C content is preferably set to 0.001% or more.
[0022] Silicon: 0.01 to 1.0% Silicon is an element that has a deoxidizing effect. In order to adequately deoxidize steel, the silicon content is set to 0.01% or more. However, if the silicon content exceeds 1.0%, the steel hardens and the forgeability decreases, and the toughness after the part is formed also decreases significantly. For this reason, the silicon content is set to 1.0% or less.
[0023] Mn: 0.010~1.0% The Mn content is set to 0.010% or more to ensure sufficient deoxidation. However, if the Mn content exceeds 1.0%, the steel will harden and forgeability will decrease. For this reason, the Mn content is set to 1.0% or less.
[0024] Ni: 0.05 to 3.0% Ni has the effect of suppressing brittle cracking of the ferrite phase. For this reason, the Ni content is set to 0.05% or more. However, if the Ni content exceeds 3.0%, the austenite phase appears at high temperatures, and the steel begins to harden by quenching, significantly reducing forgeability. For this reason, the Ni content is set to 3.0% or less.
[0025] Cr: 10.5~25.0% Cr improves corrosion resistance and improves the intergranular corrosion resistance of the weld heat affected zone. Therefore, the Cr content is set to 10.5% or more. The Cr content is preferably set to 12.0% or more, and more preferably set to 15.0% or more. However, if the Cr content exceeds 25.0%, the forge formability is significantly reduced. Therefore, the Cr content is set to 25.0% or less. The Cr content is more preferably set to 20.0% or less.
[0026] Cu: 0.02-1.0% Cu has the effect of improving corrosion resistance, and improves the intergranular corrosion resistance of the weld heat affected zone. Therefore, the Cu content is set to 0.02% or more. However, if Cu is contained in excess of 1.0%, brittle cracking is more likely to occur. Therefore, the Cu content is set to 1.0% or less. The Cu content is preferably set to 0.8% or less.
[0027] N: 0.001 to 0.03% N is an impurity that is inevitably mixed into steel. N precipitates chromium nitrides in the heat-affected zone of welding, reducing intergranular corrosion resistance. In order to suppress intergranular corrosion, it is effective to reduce the N content as much as possible. In this case, if the N content exceeds 0.03%, the Nb or Ti content required to suppress sensitization increases. As a result, the manufacturing cost increases, and the forgeability decreases due to the formation of Nb nitrides or Ti carbides. For this reason, the N content is set to 0.03% or less. It is preferable to reduce N as much as possible, but excessive reduction increases the manufacturing cost. For this reason, the N content is preferably set to 0.001% or more.
[0028] Nb: 0.10-1.0%, Nb has the effect of suppressing sensitization of the welded heat affected zone and improving corrosion resistance by forming carbides or nitrides. For this reason, the Nb content is set to 0.10% or more. Here, the appropriate amount of Nb content is affected by the C content and N content, but in order to suppress sensitization, the Nb content is set to 0.10% or more. However, if Nb is contained in an amount exceeding 1.0%, coarse carbonitrides such as NbCN or Laves phases are formed, which significantly reduces intergranular corrosion resistance, toughness, and forgeability. For this reason, the Nb content is set to 1.0% or less. The Nb content is preferably set to 0.8% or less.
[0029] The ferritic stainless steel bar according to the present invention may contain the following elements, in addition to the above elements, as necessary.
[0030] Mo: 0-3.0% Mo significantly improves corrosion resistance and also strengthens grain boundaries to suppress grain boundary cracking. However, if the Mo content exceeds 3.0%, hardening occurs and forgeability decreases. For this reason, the Mo content is set to 3.0% or less. The Mo content is preferably set to 2.0% or less, and more preferably set to 1.5% or less. On the other hand, in order to obtain the above effects, the Mo content is preferably set to 0.01% or more. The Mo content is preferably set to 0.10% or more, and more preferably set to 0.30% or more.
[0031] Ti: 0-0.5%, V: 0~1.0%, W: 0 to 0.50%, Zr: 0 to 0.50% Ti, V, Zr, and W, like Nb, form carbonitrides and thus have the effect of suppressing sensitization of welds. Therefore, they may be included as necessary. However, excessive inclusion of Ti, V, Zr, and W reduces forgeability. Therefore, the Ti content is set to 0.5% or less. The V content is set to 1.0% or less. The W content is set to 0.50% or less. The Zr content is set to 0.50% or less. However, in order to obtain the above effect, the Ti content is preferably set to 0.05% or more. Furthermore, the V content is preferably set to 0.01% or more. Furthermore, the W content is preferably set to 0.05% or more. The Zr content is preferably set to 0.010% or more.
[0032] B: 0~0.010% B suppresses P segregation at grain boundaries and improves toughness. Therefore, it may be contained as necessary. However, if B is contained in an amount exceeding 0.010%, coarse borides are formed, and toughness is deteriorated. Therefore, the B content is set to 0.010% or less. On the other hand, in order to obtain the above effect, the B content is preferably set to 0.0003% or more.
[0033] The ferritic stainless steel bar according to the present invention may contain, in addition to the above elements, one or more elements selected from Al, Ca and Mg, if necessary. Al: 0-0.50%, Ca: 0-0.05%, Mg: 0-0.05%, Al, Ca, and Mg all have a deoxidizing effect, and are therefore added as deoxidizing agents during melting. Therefore, they may be included as necessary. However, excessive inclusion of the above-mentioned Al, Ca, and Mg reduces forgeability. For this reason, the Al content is set to 0.50% or less. The Ca content is set to 0.05% or less. The Mg content is set to 0.05% or less. On the other hand, in order to obtain the above effects, the Al content is preferably set to 0.001% or more. The Ca content is preferably set to 0.0005% or more. The Mg content is preferably set to 0.0005% or more.
[0034] Co: 0 to 0.50% Co has the effect of improving hardenability and wear resistance. Therefore, it may be contained as necessary. However, if the Co content exceeds 0.50%, the toughness deteriorates. Therefore, the Co content is set to 0.50% or less. On the other hand, in order to obtain the above effects, the Co content is preferably set to 0.01% or more.
[0035] Ga: 0 to 0.05% Ga has the effect of improving corrosion resistance, so it may be contained as necessary. However, if Ga is contained in excess, forgeability decreases. For this reason, the Ga content is set to 0.05% or less. On the other hand, in order to obtain the above effect, the Ga content is preferably set to 0.001% or more.
[0036] Sn: 0 to 0.50% Sn has the effect of improving intergranular corrosion resistance. Therefore, it may be contained as necessary. However, if the Sn content exceeds 0.50%, the toughness and forgeability deteriorate due to grain boundary segregation. Therefore, the Sn content is set to 0.50% or less. On the other hand, in order to obtain the above effect, the Sn content is preferably set to 0.010% or more.
[0037] Sb: 0-0.50%, Sb has the effect of improving intergranular corrosion resistance. Therefore, it may be contained as necessary. However, if the Sb content exceeds 0.50%, the toughness and forgeability deteriorate due to segregation of Sb. Therefore, the Sb content is set to 0.50% or less. On the other hand, in order to obtain the above effect, the Sb content is preferably set to 0.010% or more.
[0038] Ta: 0 to 0.50% Ta has the effect of improving wear resistance and intergranular corrosion resistance. Therefore, it may be contained as necessary. However, if the Ta content exceeds 0.50%, toughness and forgeability deteriorate. Therefore, the Ta content is set to 0.50% or less. On the other hand, in order to obtain the above effect, the Ta content is preferably set to 0.01% or more.
[0039] REM: 0~0.10% REM has a deoxidizing effect. It also has an effect of improving hot workability. Therefore, it may be contained as necessary. However, if the REM content exceeds 0.10%, the hot workability is deteriorated. Therefore, the REM content is set to 0.10% or less. On the other hand, in order to obtain the above effects, the REM content is preferably set to 0.001% or more. REM is a collective term for 17 elements, including 15 lanthanoid elements, Y, and Sc. One or more of these 17 elements can be contained in steel, and the REM content refers to the total content of these elements.
[0040] In the chemical composition of the steel sheet of the present invention, the balance is Fe and unavoidable impurities. Here, "unavoidable impurities" refers to components that are mixed in due to various factors in raw materials such as ores and scraps and manufacturing processes when industrially manufacturing steel sheets, and are acceptable within a range that does not adversely affect the present invention. Examples of unavoidable impurities include S, P, O, Zn, Pb, and H. It is desirable to reduce the amount of unavoidable impurities, but if they are contained, it is desirable to keep the amount to 0.01% or less.
[0041] Here, the ferritic stainless steel bar according to the present invention satisfies the following formula (i) in order to form Nb carbonitrides and suppress a decrease in intergranular corrosion resistance. 10.0≦(Nb+Ti) / (C+N) ···(i) In the above formula, each element symbol represents the content (mass%) of each element contained in the steel, and when no element is contained, the symbol is set to zero. If the value on the right side of the formula (i) is less than 10.0, Nb carbonitrides are not sufficiently formed, Cr deficiency occurs, and corrosion resistance decreases. Therefore, the value on the right side of the formula (i) is set to 10.0 or more, preferably 12.0 or more, and more preferably 15.0 or more. Although there is no particular upper limit for the value on the right side of the formula (i), it is usually about 100.0.
[0042] Further, the ferritic stainless steel bar according to the present invention satisfies the following formula (ii) in order to ensure sufficient toughness while maintaining excellent intergranular corrosion resistance. 12.0≦Cr+3(Mo+Ni)+(Nb+Ti)-10(C+N)≦30.0 (ii) In the above formula, each element symbol represents the content (mass%) of each element contained in the steel, and when no element is contained, the symbol is set to zero. If the value of the middle side of the formula (ii) is less than 12.0, the intergranular corrosion resistance cannot be ensured, and sensitization is likely to occur. Therefore, the value of the middle side of the formula (ii) is set to 12.0 or more, preferably 13.0 or more, more preferably 14.0 or more, and even more preferably 16.0 or more. On the other hand, if the value of the middle side of the formula (ii) exceeds 30.0, the toughness decreases and brittle cracking is likely to occur. Therefore, the value of the middle side of the formula (ii) is set to 30.0 or less, and even more preferably 25.0 or less.
[0043] 2.Types and distribution of precipitates In general, various precipitates such as Nb(C,N) (hereinafter referred to as Nb carbonitride), M6C, and Laves phase are precipitated in ferritic stainless steel rods. In particular, the Laves phase becomes the starting point of brittle cracking, and the toughness is reduced. The Laves phase easily becomes the starting point of brittle cracking because it precipitates in a needle shape, which concentrates stress. In the present invention, fixing Nb by Nb carbonitride or M6C is effective in suppressing the Laves phase. For this reason, in the ferritic stainless steel rod according to the present invention, Nb carbonitride and / or M6C are detected in the extraction residue recovered by electrolytic extraction using a 0.2 μm mesh filter, and the X-ray diffraction intensity of the 112 plane of the Laves phase is less than 20% of the X-ray diffraction intensity of the 111 plane of the Nb carbonitride. In comparing the Laves phase and the Nb carbonitride, the 112 plane of the Laves phase and the 111 plane of the Nb carbonitride were selected as representative peaks of the respective precipitates.
[0044] In addition, Nb carbonitrides precipitate coarsely in the center during casting, and are likely to become the starting point of brittle cracks. In the present invention, it is effective to suppress coarse Nb carbonitrides by eliminating segregation in the center by soaking and controlling the total residence time at 1100°C or higher during hot rolling. For this reason, the ferritic stainless steel bar according to the present invention has a number density of 1000 precipitates / mm2 of coarse precipitates with a maximum diameter of 5 μm or more, which are distributed within a range of up to 1 / 4 of the diameter from the center of the bar on both sides in the radial direction and 5 mm in the longitudinal direction, in a cross section including the center of the bar and parallel to the longitudinal direction and radial direction. 2 The number density of coarse precipitates is 800 pieces / mm 2 Preferably less than 500 pieces / mm 2 Less than 300 pieces / mm is more preferable. 2 The lower limit of the number density is preferably 10 particles / mm. 2 That's all.
[0045] The type of precipitates was investigated using the following procedure. First, a bar-shaped steel material was cut into a plate material with a thickness of 2 to 3 mm parallel to the longitudinal and radial directions including the center, and the surface area of the plate was 5 to 20 cm2. 2 The longitudinal width is adjusted so that the precipitates are separated from the steel cross section by the extraction residue method, the residue is collected using a 0.2 μm mesh filter, and the peak position (2θ) and peak intensity (cps) are analyzed by XRD structure analysis. At this time, the background (noise) may be adjusted using software. The precipitates are identified by referring to a database, and if the peak position in the database is on the analytical peak position, it is determined that the corresponding precipitate has precipitated. The database is referred to PDF numbers 03-065-8772 (Nb carbonitride), 00-017-0128 (M6C), and 00-017-0908 (Laves phase). After identifying the precipitates from the database, for each precipitate with a specific crystal plane, the peak intensities of the Nb carbonitride 111 plane (35.2°), M6C5 11 plane (41.5°), and Laves phase 112 plane (44.1°) are used. The peak intensity corresponds to the X-ray diffraction intensity.
[0046] The number density of coarse precipitates is investigated using the following procedure. First, a cross section parallel to the longitudinal and radial directions is cut from the center of a bar-shaped steel material, mirror polished and etched, and then observed under an optical microscope. An area extending from the center to a diameter of 4 in both radial directions and 5 mm in the longitudinal direction is observed at a microscope magnification of 100 to 1000 times, and precipitates with a maximum diameter of 5 μm or more are counted using image analysis, and the number density is calculated by dividing the number by the observation area.
[0047] 3.Diameter The diameter of the ferritic stainless steel bar according to the present invention is not particularly specified, but in order to forge large parts involving welding, the diameter is preferably 16 mm or more, and the upper limit of the diameter is preferably 100 mm or less.
[0048] 4. Toughness The toughness of the ferritic stainless steel bar according to the present invention is evaluated using the ductile-brittle transition temperature in a Charpy impact test. A Charpy test piece conforming to JIS Z 2242 is used, including the region from the center (D / 2 part) to the D / 4 part of the bar, with the surface layer as the reference. The length direction of the test piece is the rolling direction of the bar, and the notch of the test piece is a U-notch. If the transition temperature is 150°C or less, the toughness is judged to be good. For toughness, the transition temperature is preferably 100°C or less, and more preferably 50°C or less.
[0049] 5. Forged parts with welding By subjecting the ferritic stainless steel bar material according to the present invention to forging, cutting, etc., it is possible to obtain a forged part having good toughness while maintaining intergranular corrosion resistance in the weld heat affected zone. The welding method is not particularly specified, but examples thereof include MIG welding, MAG welding, TIG welding, laser welding, and resistance welding.
[0050] 6. Manufacturing method A preferred method for producing the ferritic stainless steel bar according to the present invention will be described below. The ferritic stainless steel bar according to the present invention can obtain the effects as long as it has the above-mentioned configuration regardless of the production method, but can be stably produced, for example, by the following production method.
[0051] The slab is soaked at 800°C to 1250°C for a holding time of 60 to 600 minutes. This can reduce coarse Nb carbonitrides while eliminating segregation in the center of the slab. If the steel exceeds 1250°C, the surface is significantly oxidized and the yield decreases, so the slab is held at 1250°C or less. 1200°C or less is preferable, and 1150°C or less is more preferable. On the other hand, if the temperature is controlled to less than 800°C, it may be difficult to eliminate segregation in the center and coarse precipitates may easily precipitate, so the slab is held at 800°C or more. 850°C or more is preferable, and 900°C or more is more preferable. If the holding time is less than 60 minutes, the time to eliminate the segregation in the center is insufficient, and coarse precipitates are likely to precipitate, so the holding time is set to 60 minutes or more. 120 minutes or more is preferable, and 180 minutes or more is more preferable. On the other hand, if the holding time exceeds 600 minutes, the amount of coarse Nb carbonitrides precipitated becomes excessive, which actually reduces toughness, so the holding time is set to 600 minutes or less. 540 minutes or less is preferable, and 480 minutes or less is more preferable.
[0052] In hot rolling, if the steel material is allowed to stay at 1100°C or higher for 10 minutes or more, the Nb carbonitrides will coarsen during rolling, so the stay time at 1100°C or higher is set to less than 10 minutes. The total residence time at 800 to 1100°C during hot rolling is controlled to 30 to 300 minutes. Here, the total residence time refers to the total time at 800 to 1100°C during heating, hot rolling, and cooling. By controlling the total residence time at 800 to 1100°C, it becomes easier to obtain M6C of an appropriate form, and the precipitation of the Laves phase is delayed. In addition, if the total residence time at 800 to 1100°C during hot rolling is less than 30 minutes, the steel material is rolled without being heated evenly, and there is a possibility that the distribution of precipitates will become uneven. For this reason, the total residence time is set to 30 minutes or more. On the other hand, if the total residence time exceeds 300 minutes, excessive M6C will precipitate, which will rather reduce toughness. For this reason, the total residence time is set to 300 minutes or less.
[0053] The rolled material is hot rolled to a finishing temperature in the range of 780 to 1100°C, then cooled to 750°C at an average cooling rate of 5 to 200°C / min, and then cooled from 750°C to 550°C at an average cooling rate of 50 to 500°C / min. If the finishing temperature is less than 780°C, the Laves phase precipitates and the toughness decreases, so it is set to 780°C or higher. The finishing temperature is preferably 800°C or higher, more preferably 850°C or higher, and even more preferably 900°C or higher. On the other hand, if it exceeds 1100°C, the amount of solute Nb increases due to the solution of M6C, making it easier for the Laves phase to precipitate, so it is set to 1100°C or lower. The finishing temperature is preferably 1050°C or lower, and more preferably 1000°C or lower. At temperatures above 750°C, M6C is more likely to precipitate than the Laves phase, and slow cooling at high temperatures to remove strain and precipitate M6C is effective in suppressing the Laves phase. For this reason, the average cooling rate is 200°C / min or less to 750°C. 180°C / min or less is preferable, and 150°C / min or less is more preferable. On the other hand, if the average cooling rate to 750°C is less than 5°C / min, the Laves phase will precipitate during the cooling process and the toughness will decrease. For this reason, the average cooling rate to 750°C is set to 5°C / min or more. 10°C / min or more is preferable, and 20°C / min or more is more preferable. The range of 750 to 550°C is a region where the Laves phase is more likely to precipitate than M6C, and the precipitation of the Laves phase can be suppressed by rapid cooling by forced air cooling or water cooling. For this reason, the average cooling rate at 750 to 550°C is set to 50°C / min or more. 80°C / min or more is preferable, and 100°C / min or more is more preferable. On the other hand, cooling that is too rapid will not be able to remove the strain in time, leading to increased costs for re-annealing, etc. For this reason, the average cooling rate at 750 to 550°C is set to 500°C / min or less. 450°C / min or less is preferable, and 400°C / min or less is more preferable.
[0054] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. EXAMPLES
[0055] Steels having the chemical compositions shown in Tables 1 and 2 were melted in a 100 kg vacuum melting furnace, cast into slabs with a diameter of 180 mm, and soaked at 900°C for 10 hours (600 minutes). The slabs were then heated at 1050°C and hot rolled to a diameter of 65 mm. The hot rolling finishing temperature was 900°C, the average cooling rate to 750°C was 50°C / min, the average cooling rate from 750 to 550°C was 300°C / min, and the residence time at 800 to 1100°C was 100 minutes. Then, pickling (peeling) was performed to obtain steel bars. In Tables 2 to 6 below, values outside the specifications of the bar-shaped steel material of the present invention, values outside the preferred manufacturing method range of the present invention, and values outside the target quality of the present invention are underlined.
[0056] [Table 1]
[0057] [Table 2]
[0058] (Identification of precipitates) The precipitates were identified for the obtained steel bar by the following method. Plate-shaped test pieces of (diameter) x 10 x 2 mm including a cross section parallel to the longitudinal direction and diameter direction of the steel bar were cut out. Electrolytic extraction was performed with an acetylacetone-based nonaqueous electrolyte, and the extraction residue was collected with a 0.2 μm mesh filter and subjected to XRD analysis. The sampling width was 0.008°, the scan speed was 0.8° / min, the voltage was 40 V, and the current was 200 mA, and the 2θ range was measured from 20 to 80°. After identifying the precipitates from the database, the peak intensities of the Nb carbonitride 111 plane (35.2°), M6C511 plane (41.5°), and Laves phase 112 plane (44.1°) were measured and used as the X-ray diffraction intensity. It was determined that the Nb carbonitride and / or M6C precipitates were contained when the peak intensity of the Nb carbonitride 111 plane and / or M6C511 plane had a finite value.
[0059] (Number density of coarse precipitates in the center of the steel material) The number density of precipitates in the centre of the steel material was measured using the following method. A sample with a longitudinal width of 5 mm was cut out from a cross section parallel to the longitudinal and diametric directions, including the centre of the steel bar. Mirror polishing and etching were performed, and the area from the centre to a quarter of a diameter on both sides in the radial direction was observed at 200x using an optical microscope. The number of precipitates with a maximum diameter of 5 μm or more was counted using image analysis, and the number density was calculated by dividing by the measured area. In the item for number density of central coarse precipitates in the table, ◎ indicates 500 precipitates / mm 2 Below, ○ indicates 501-800 pieces / mm 2 Below, △ indicates 801~1000 pieces / mm 2 The following is shown. × indicates 1000 pieces / mm 2 The above is shown.
[0060] (Toughness evaluation) A Charpy test was used to evaluate toughness. A standard test piece conforming to JIS Z 2242 was used, including the area from the center of the steel material (D / 2 part) to D / 4 part, with the surface layer as the base layer. The length direction of the test piece was the rolling direction of the bar-shaped steel material, and the notch of the test piece was a U-notch. If the energy transition temperature was 150℃ or less, it was determined that the toughness was good.
[0061] (Intergranular corrosion resistance evaluation) A modified Strauss test, an improved version of the JIS G 0575 test solution, was used to evaluate the intergranular corrosion resistance of welded heat-affected zones. Two pieces of 2mm-thick bar steel were cut in the longitudinal direction, and spot welding was performed on the cut surfaces. The test solution was a boiled solution of 0.5% sulfuric acid + 5% copper sulfate, and the test pieces were immersed for 16 hours while in contact with the copper pieces. The cross section of the welded part of the test piece was cut out and mirror-polished, and the intergranular corrosion condition around the welded part was observed with an optical microscope. If no grains had fallen off, the intergranular corrosion resistance was determined to be good.
[0062] [Table 3]
[0063] [Table 4]
[0064] Test Nos. 1 to 35 satisfied the compositional requirements of the present invention and were excellent in toughness and intergranular corrosion resistance, whereas Test Nos. 36 to 51, which did not satisfy the compositional requirements of the present invention, were poor in toughness or intergranular corrosion resistance. EXAMPLES
[0065] Steel type No. 1 shown in Table 1 was melted in the same manner as in Example 1 to produce a slab with a diameter of 180 mm. Hot rolling was performed under various rolling conditions to produce steel bars with diameters of 16 to 100 mm. As in Example 1, precipitates were identified, the number density of coarse precipitates in the center of the steel was measured, and toughness and intergranular corrosion resistance were evaluated. The implementation conditions and results are summarized in Tables 5 to 6.
[0066] [Table 5]
[0067] [Table 6]
[0068] Test Nos. 52 to 71 satisfied the preferred manufacturing conditions of the present invention, and were good in toughness and intergranular corrosion resistance. Test Nos. 72 to 76 did not satisfy some of the preferred manufacturing conditions of the present invention, and therefore the number density of the central coarse precipitates was out of the preferred range, but the transition temperature and intergranular corrosion resistance were within the preferred range of the present invention. On the other hand, Test Nos. 77 to 85, which did not satisfy the preferred manufacturing conditions of the present invention, had excessive precipitation of the Laves phase, and therefore had poor toughness or poor intergranular corrosion resistance. [Industrial Applicability]
[0069] The ferritic stainless steel bar according to the present invention has good forgeability. Furthermore, structural parts forged using the ferritic stainless steel bar according to the present invention do not suffer from sensitization in the weld heat-affected zone, have good intergranular corrosion resistance, and have good toughness, even when assembled and manufactured using welding such as laser welding or MIG welding. For this reason, the ferritic stainless steel bar is suitable for automotive structural parts, such as exhaust system flanges, high-pressure fuel pumps, boss materials, injectors, etc.
Claims
1. The chemical composition, in mass%, is C: 0.001-0.03%, Si: 0.01-1.0%, Mn: 0.010 to 1.0%, Ni: 0.05-3.0%, Cr: 10.5-25.0%, Cu: 0.02-1.0%, N: 0.001-0.03%, Nb: 0.10-1.0%, Mo: 0-3.0%, Ti: 0 to 0.5%, V: 0 to 1.0%, W: 0-0.50%, Zr: 0 to 0.50%, B: 0 to 0.010%, Al: 0-0.50%, Ca: 0-0.05%, Mg: 0-0.05%, Co: 0 to 0.50%, Ga: 0-0.05%, Sn: 0 to 0.50%, Sb: 0 to 0.50%, Ta: 0 to 0.50%, REM: 0-0.10%, The balance is Fe and impurities. The following formulas (i) to (ii) are satisfied: Electrolytic extraction was carried out from a bar-shaped steel material using an acetylacetone-based non-aqueous electrolyte, and the extraction residue was collected through a 0.2 μm mesh filter, and Nb carbonitride and / or M were added to the extraction residue. 6 A ferritic stainless steel bar material containing precipitates of C, and in which the X-ray diffraction intensity of the (112) plane of the Laves phase is less than 20% of that of the (111) plane of the Nb carbonitride. 10.0≦(Nb+Ti) / (C+N)...(i) 12.0≦Cr+3(Mo+Ni)+(Nb+Ti)-10(C+N)≦30.0...(ii) In the above formula, each element symbol represents the content (mass%) of each element contained in the steel, and when the element is not contained, it is set to zero.
2. The chemical composition, in mass percent, Mo: 0.01-3.0%, Ti: 0.05-0.5%, V: 0.01-1.0%, W: 0.05-0.50%, Zr: 0.010 to 0.50%, B: 0.0003 to 0.010%, Al: 0.001-0.50%, Ca: 0.0005-0.05%, Mg: 0.0005-0.05%, Co: 0.01 to 0.50%, Ga: 0.001-0.05%, Sn: 0.010-0.50%, Sb: 0.010 to 0.50%, Ta: 0.01 to 0.50%, REM: 0.001-0.10%, The ferritic stainless steel bar according to claim 1, comprising one or more selected from the following:
3. In a cross section including the center of the bar-shaped steel material and parallel to the longitudinal and radial directions, the number density of precipitates with a maximum diameter of 5 μm or more distributed within a range of 1 / 4 of the diameter from the center of the bar-shaped steel material on both sides in the radial direction and within a range of 5 mm in the longitudinal direction is 1000 pieces / mm 2 The ferritic stainless steel bar according to claim 1 or 2, wherein:
4. The ferritic stainless steel bar according to any one of claims 1 to 3, wherein the transition temperature at the center of the steel material in a Charpy test is 150°C or less.
5. The method for producing a steel material having the composition according to claim 1 or 2, wherein the holding temperature of the slab soaking is 800 to 1250°C and the holding time is 60 to 600 minutes.
6. The method for producing a ferritic stainless steel bar according to claim 5, wherein the residence time at 1100°C or higher during hot rolling is 10 minutes or less, the total residence time at 800 to 1100°C is 30 to 300 minutes, the finishing temperature is 780 to 1100°C, the average cooling rate to 750°C is 5 to 200°C / min, and the average cooling rate from 750°C to 550°C is 50 to 500°C / min.
Citation Information
Patent Citations
High toughness stainless steel and its manufacture
JP1991126843A
Ferritic stainless steel wire rod and steel wire, and method for producing them
JP2013147705A
Ferritic stainless linear steel material for fastening component
JP2017066431A
Ferritic stainless steel sheet
JP2020143309A
Ferritic stainless steel bar, automobile fuel system component and automobile fuel system member
JP2021038439A